Pre-Breeding Considerations for the Development of Replacement Beef Heifers - Pedro L. P. Fontes; Nicky Oosthuizen; Carla D. Stanford; G. Cliff Lamb (EDIS)
The efficiency of post-weaning development of heifers has a major impact on the overall profitability of cow-calf operations. To ensure satisfactory performance during the first breeding season, replacement heifers must be subjected to an adequate development program. This 3-page fact sheet covers age at puberty, nutrition, target body weight gain, pelvic area measurements, reproductive tract score, and herd health. Written by Pedro L. P. Fontes, Nicky Oosthuizen, Carla D. Sanford, and G. Cliff Lamb, and published by the UF Department of Animal Sciences, November 2016.